A Double‐Moment SBU‐YLIN Cloud Microphysics Scheme and Its Impact on a Squall Line Simulation. (8th November 2021) - Zhao, Xi; Lin, Yanluan; Luo, Yali; Qian, Qifeng; Liu, Xi; Liu, Xiantong; Colle, Brian A.
Abstract: A double‐moment version of the SBU‐YLIN cloud microphysical scheme in WRF is introduced. It predicts the mass and number mixing ratios of cloud droplet, rain, cloud ice, and precipitating ice. In addition, a number of physical processes, like rain evaporation, collection between rain and snow are also optimized in the new scheme. The scheme is evaluated and compared with the original one‐moment scheme for a squall line case. We found that the double‐moment approach gives a better representation of rain evaporation, which is critical for the development, morphology, and evolution of the simulated squall line, especially for the enhanced trailing stratiform cloud and leading convective line. The relationship between key microphysical processes and squall line dynamics is investigated to identify the driving mechanisms of the descending rear inflow, cold pool, and slantwise updraft. Furthermore, formation of the transition zone in the simulated squall line strongly depends on the flexible description of ice particle properties, such as size, degree of riming and fall speed. Plain Language Summary: A double‐moment version of the SBU‐YLIN cloud microphysical scheme in WRF is introduced and evaluated. The scheme improves a squall line simulation in terms of the shape and structure of the squall line with enhanced stratiform precipitation. The improvement is mainly related to more realistic rain evaporation and flexible description of ice particle properties. Close interactions between cloud and precipitation physics and dynamics is key for the development, maintenance and movement of squall lines. Key Points: A double‐moment version of the SBU‐YLIN scheme is introduced The scheme improves the simulation of a squall line in terms of the transition zone and stratiform precipitation Rain evaporation and flexible description of ice particles are critical for a realistic simulation